MIG/MAG RSSP (com reversão sincronizada do sentido da tocha e da polaridade) visando automação de soldagem do passe de raiz em tubulações - Skhabovskyi, Iaroslav (2014)
One of the biggest concerns in automated (mechanized) welding of root passes is the robustness of bead geometry in response to utilized parameters and operational conditions. Skilled welder is able to control the weld pool from visual information, regardless of variation in the root opening (gap) and/or misalignment in the groove. However, there is no sensor and actuator capable of mimicking the ability of the welder to identify the condition of the pool and move the arc to face anomalies present in automated (mechanized) welding. One solution to avoid the typical problems of the root pass (burn-through, for example) is the use of backing. However, this feature increases the cost and production time. Thus, to accomplish automatic welding of root passes it would be necessary to develop a process/technique robust enough to maintain a stable pool even with geometric variations (high-low and misalignment of the joint faces) on the grooves. Then, pipe welding could be carried out with less time and cost. Thus, the objective of this work is to innovatively develop and evaluate, in an original manner, a GMAW technique based on the control of the type of current and torch motion, in order to prevent the collapse of the weld pool under different geometric tolerances of joint preparation. For this, a particular welding power source controlled by motion sensors for synchronizing a type of operating mode of the process with the position of the arc in the joint (sides and center of the groove) was used. To allow a better distribution of heat in the joint, a welding pass was made on the sides of the groove with DCEP polarity pulsed (more heat input) and a central pass was performed with DCEN polarity in constant current mode or Short Circuit Controlled DCEN polarity (less heat input and arc pressure). The evaluation of this process involved verification of parameters affecting weld bead visual quality and process stability. The results show the feasibility of the technique for enabling automatic welding of root passes in the flat position with variations of the root opening (gap) of ± 0.5 mm and with high-low up to 3 mm.